TACIT KNOWLEDGE AS A SOURCE OF COMPETITIVE ADVANTAGE IN THE NATIONAL BASKETBALL ASSOCIATION. - Berman, S. L.; Down, J.; Hill, C. W. L. (Academy of Management Journal, 2002)
In this study, we investigate a central tenet of the resource-based view of the firm舒that tacit knowledge often lies at the core of sustainable competitive advantage舒and attempt to articulate it wi...